Financially Feasible and Sustainable - Reviewing Academic Literature on Sustainability related Investment Studies - Happonen, Ari; García-Alcaraz, Jorge Luis; Potdar, Apurva; Laplaza Osta, Irene (B P International, 2021)
https://stm.bookpi.org/FFSRALSIS/article/view/3906